(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Software quality is important to developers, businesses, and governments. As is well-known, software maintainability determines quality. Coupling measurement is one way to benchmark an application’s maintainability. Static code analysis is used in traditional measurement techniques during system testing or trial operations. When we were using COBOL, FORTRAN, Pascal, and C, static analysis was helpful. Dynamic coupling may be used to assess systems and applications with the emergence of object-oriented (OO) languages like C++, Visual C, and Java. Dynamic coupling matches the reality of the tested application since it can uncover problems and shortages that are not predicted with static coupling. Dynamic coupling, on the other hand, requires a lot longer to quality-test, particularly if the subject application is substantial.